TrendTV: An architecture for automatic change of TV channels based on social networks with multiple device support - Sena, H. T. A.; Dias, R.; de Melo, Julio Paulino; Burlamaqui, Aquiles M. F. (2011 IEEE International Conference on Virtual Environments, Human-Computer Interfaces and Measurement Systems Proceedings, 2011)
In this work, we present the TrendTV architecture, a set of software layers that links various TV show viewers, producing a personalized recommendation system. In this architecture is possible to indicate the quality of a TV show in real time through the interaction between viewers using a social network that can be accessed through several different ways. Associated with a personalized Electronic Programming Guide, this social network allows the viewer to perform filtering on a particular subject from the indication made by other viewers through the interactivity over the Web, interactive TV or through a mobile device. The result is a dynamic database containing the classification of several TV programs built from that architecture, and an application that change automatically to the best channel at the moment.